Analysis of starch from trunking and non-trunking sago palm (metroxylon sago sp.) - Mohd Izzuddin, Alias (Universiti Malaysia Sarawak (UNIMAS), 2012)
The starch content of sago palm (Metroxylon sagu sp.) is in its trunk. This study was carried out to investigate the proper methods to analyse starch from trunking and non-trunking sago palms. Sago palm is also one of the oldest tropical plants exploited by man for its stem starch and one of the main starch-producing crops in the world. The method used to analyse the starch was by doing the leaf starch granule extraction where starch was extracted and observed under the scanning electron microscope. To analyse the glucose content, the boiling starch and Bicinchoninic Acid (BCA) assay were used. The iodine test was used to determine the starch content. At 95% confidence level, test statistic was 2.3059, which falls in critical regions, the null hypothesis was accepted indicate there is no significant different in starch content of trunking and non-trunking sago palm. The size and the shape of starch granules also were viewed and determine. For the trunking and non-trunking sago palm trunk, the size of starch granules range from 10 μm to 20 μm. While for the trunking and non-trunking sago palm leaves, the size of starch granules range from 1 μm to 5 μm.